2021
DOI: 10.1021/acs.jmedchem.1c00939
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Identification of Novel Antibacterial Agents against Planktonic Growth and Biofilm Formation of Enterococcus faecalis

Abstract: YycFG, one of the two-component systems involved in the regulation of biofilm formation, has attracted increasing interest as a potential target of antibacterial and antibiofilm agents. YycG inhibitors for Staphylococcus aureus and Staphylococcus epidermidis have been developed, but Enterococcus faecalis remains underexplored. Herein, we selected and identified novel candidate molecules against E. faecalis targeting histidine kinase YycG using high-throughput virtual screening; six molecules (compound-16, -30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The reported YycG HK inhibitors included three different classes of chemical structures: indoles, 2,4‐thiazolidinediones, and pyrrolidones. Among these inhibitors, a typical compound 16, which had an indole core with benzenesulfonyl and ester groups, showed effectively antibacterial and anti‐biofilm activity, exhibited low cytotoxicity on mammalian cells and was not hemolytic [18] (Scheme 1). Compared with vancomycin and ampicillin, compound 16 had a better inhibition effect on E. faecalis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported YycG HK inhibitors included three different classes of chemical structures: indoles, 2,4‐thiazolidinediones, and pyrrolidones. Among these inhibitors, a typical compound 16, which had an indole core with benzenesulfonyl and ester groups, showed effectively antibacterial and anti‐biofilm activity, exhibited low cytotoxicity on mammalian cells and was not hemolytic [18] (Scheme 1). Compared with vancomycin and ampicillin, compound 16 had a better inhibition effect on E. faecalis .…”
Section: Introductionmentioning
confidence: 99%
“…According to the docking test between compound 16 and YycG protein which had been studied by Yu et al., [18] it was found that the inhibitor had one hydrogen bond acceptor, hydrogen bonding to Asn501, Ser571, and Lys572; two hydrophobic groups, hydrophobic groups fit into two hydrophobic cavities including Leu536, Ile538, Tyr509 and Phe594, Val546, Phe547 amino acid residues locating inside and outside YycG protein, respectively. In this article, a series of 2‐alkyl‐5‐((phenylsulfonyl)oxy)‐1 H ‐indole‐3‐carboxylate derivatives with benzenesulfonyl and ester groups were designed and synthesized to expect to obtain several targeted histidine kinase inhibitors with good anti‐bacterial and anti‐biofilm activities.…”
Section: Introductionmentioning
confidence: 99%
“…9 Small molecular inhibitors can inhibit the autophosphorylation of YycG by binding to the HATPase_c domain or HisKA domain, thereby inhibiting bacterial growth and biofilm formation. 10 Hence, histidine kinase (HK) of bacterial two-component systems becomes a potential antibacterial target. 11 Multiple reports have demonstrated the effective development of antimicrobial molecules against B. subtilis (Walkmycin C), 12 S. aureus (Aranorosinol B), 13 and E. faecalis (Waldiomycin) 14 by targeting YycG histidine kinase.…”
mentioning
confidence: 99%
“…11 Multiple reports have demonstrated the effective development of antimicrobial molecules against B. subtilis (Walkmycin C), 12 S. aureus (Aranorosinol B), 13 and E. faecalis (Waldiomycin) 14 by targeting YycG histidine kinase. In our previous study, some novel inhibitors of YycG histidine kinase including thiazolidones, 15 thiazolopyrimidinones, 16 indoles, and pyrrolidones 10 had been reported, which had potential values as leads for developing new antibiotics. Among these inhibitors, compound 62 10 (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation